Phylogenetic analysis of Pythium insidiosum Thai strains using cytochrome oxidase II (COX II) DNA coding sequences and internal transcribed spacer regions (ITS) - Patcharee Kammarnjesadakul (2018)
To investigate the phylogenetic relationship among Pythium insidiosum isolates in Thailand, we investigated the genomic DNA of 31 P. insidiosum strains isolated from humans and environmental sources from Thailand, and two from North and Central America. We used PCR to amplify the partial COX II DNA coding sequences and the ITS regions of these isolates. The nucleotide sequences of both amplicons were analyzed by the Bioedit program. Phylogenetic analysis using genetic distance method with Neighbor Joining (NJ) approach was performed using the MEGA4 software. Additional sequences of three other Pythium species, Phytophthora sojae and Lagenidium giganteum were employed as outgroups. The sizes of the COX II amplicons varied from 558-564 bp, whereas the ITS products varied from approximately 871-898 bp. Corrected sequence divergences with Kimura 2-parameter model calculated for the COX II and the ITS DNA sequences ranged between 0.0000-0.0608 and 0.0000-0.2832, respectively. Phylogenetic analysis using both the COX II and the ITS DNA sequences showed similar trees, where we found three sister groups (ATH, BTH, and CTH) among P. insidiosum strains. All Thai isolates from clinical cases and environmental sources were placed in two separated sister groups (BTH and CTH), whereas the Americas isolates were grouped into ATH. Although the phylogenetic tree based on both regions showed similar distribution, the COX II phylogenetic tree showed higher resolution than the one using the ITS sequences. Our study indicates that COX II gene is the better of the two alternatives to study the phylogenetic relationships among P. insidiosum strains. © 2011 ISHAM.